2022
DOI: 10.3390/healthcare10102041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Circuit Training on Patients with Knee Osteoarthritis: A Systematic Review and Meta-Analysis

Abstract: The most prevalent joint disease is osteoarthritis (OA), which affects an estimated 240 million individuals worldwide. Knee osteoarthritis (KOA) is one of the top 10 causes of disability worldwide. The aim of this study is to systematically evaluate the effect of circuit training (CT) on patients with KOA. We searched through PubMed, Scopus, ScienceDirect, Cochrane, and Google Scholar up to 12 February 2022. We used random-effects statistical analysis for continuous variables and reported the results as a stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
1
11
0
1
Order By: Relevance
“…Such an observation underlines the key role of exercise in lowering pain, increasing range of motion and flexibility as well as strengthening the knee joint muscles. In agreement with our study, a recent systematic review and metaanalysis incorporated seven trials with 346 patients diagnosed with KOA, revealing a significant reduction in the pain score following a CT program [107].…”
Section: Painsupporting
confidence: 92%
See 1 more Smart Citation
“…Such an observation underlines the key role of exercise in lowering pain, increasing range of motion and flexibility as well as strengthening the knee joint muscles. In agreement with our study, a recent systematic review and metaanalysis incorporated seven trials with 346 patients diagnosed with KOA, revealing a significant reduction in the pain score following a CT program [107].…”
Section: Painsupporting
confidence: 92%
“…Contrastingly, another study failed to identify a notable difference in TUG performance [106]. Similarly, a recent systematic review and meta-analysis revealed the absence of significant improvements in functional performance based on 30CST and TUG scores [107]. This discrepancy may be ascribed to variations in participants' baseline fitness levels, inadequate intervention duration to provoke discernible changes, potential methodological constraints, or the necessity for more specific and targeted exercise interventions.…”
Section: Musculoskeletal Fitnessmentioning
confidence: 99%
“…Together, they contribute to improved glycemic control by reducing insulin resistance and enhancing glucose metabolism ( Yavari et al, 2012 ). Additionally, aerobic exercise enhances cardiac output, vascular function, and endothelial health, while resistance training improves arterial stiffness and regulation of blood pressure ( Al-Mhanna et al, 2022b ; Okamoto, Masuhara & Ikuta, 2013 ). CART leverages these benefits, resulting in enhanced cardiovascular fitness and heart health.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of the risk of bias was previously described [ 27 ]. In summary, we checked the risk of bias based on the Cochrane Handbook for Systematic Reviews of Interventions (Figures 1 and 2 ) [ 28 ].…”
Section: Methodsmentioning
confidence: 99%